Living the Community Through Art: The Social Life of Reboan in Bale Seni Tepa Slira - Anugrahita, Tegar; Udi Utomo; Sunarto, Sunarto (Universitas Negeri Semarang, 2025)
This study investigates how a community-based art initiative—Reboan, held weekly by Bale Seni Tepa Slira in Banyumas, Indonesia—contributes to the social vitality of its participants. Emerging from grassroots artistic impulses, Reboan has evolved into a sustainable practice that bridges performance, learning, and cultural regeneration. Through a qualitative case study grounded in McMillan and Chavis’s (1986) theory of sense of community, the research examines how the dimensions of membership, influence, needs fulfillment, and shared emotional connection are manifested in the community’s everyday interactions. Data was collected through immersive fieldwork involving observation, interviews, and documentation. The findings highlight Reboan’s function not only as a platform for local artistic expression but as a space of belonging, emotional support, and mutual empowerment. As such, Reboan exemplifies the transformative potential of community art in cultivating inclusive, participatory, and socially resilient cultural ecosystems.